THE MEANING TRANSFERENCE FROM SPATIAL TO NON-SPATIAL MEANINGS OF BELOW - Long, Do Tuan; Huyen Trang, Vu Thi (VNU Journal of Foreign Studies; Vol 38 No 3DO - 10.25073/2525-2445/vnufs.4845, 2022)
This paper analyses the transference from spatial to non-spatial meanings of below as a preposition, an adverb, and a particle within the 2017 Corpus of Contemporary American English, genre: fiction. In light of the Multimodal Image Theory and Extended Conceptual Metaphor Theory, the data analysis shows that the prototypical meaning of below  has two variants in its Visual space, and two non-spatial meanings namely Less  and Inferior . The mechanism of meaning transference is mappings in which salient aspects of absence of contact, force, and occlusion between the Trajector (TR) and Landmark (LM) are retained in construing the non-spatial scenes associated with the word.